Urban Waste Governance in Jakarta: Assessing Institutional Challenges and Policy Implementation - Anis Rifai; Zuhad Aji Firmantoro; Amoury Adi Sudiro; Anas Lutfi; M. Isnanda Wendy N (Magister Ilmu Hukum, Universitas Krisnadwipayana, 2026)
Waste management failure in Jakarta is not merely a technical or environmental issue; rather, it reflects fundamental deficiencies in the regulatory framework, which has failed to generate efficient economic incentives, internalize environmental externalities, and operationalize circular economy mechanisms. Employing a socio-legal research methodology combined with a normative-economic approach, this study finds that Indonesia’s waste management regime remains predominantly governed by a command-and-control model, which has proven ineffective in influencing the economic behaviour of producers, consumers, and local governments. Structural deficiencies—including the absence of a robust Extended Producer Responsibility (EPR) framework, excessive transaction costs arising from institutional fragmentation, the inability of existing pricing structures to reflect the marginal cost of waste disposal, and the systematic exclusion of the informal waste sector—have collectively produced a governance architecture that is economically inefficient and socially inequitable. This study aims to identify and analyse the role of Economic Analysis of Law (EAL) in enhancing the efficiency and effectiveness of waste management legislation in Jakarta and to formulate an appropriate regulatory model for urban waste governance. The findings demonstrate that EAL provides a robust analytical framework for diagnosing regulatory failures and evaluating institutional inefficiencies. The study argues that reconstructing Indonesia’s waste management regulatory framework requires a transition from a predominantly punitive command-and-control approach to a comprehensive incentive-compatible regulatory system. Such reform carries significant implications for legislative development and supports the realization of the constitutional right to a good and healthy environment as guaranteed under Article 28H of the 1945 Constitution of the Republic of Indonesia. Accordingly, the proposed regulatory model should adapt international best practices to Indonesia’s institutional context, thereby aligning economic incentives with environmental sustainability and social inclusion.